2014
DOI: 10.1021/cn500038f
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lithium on Inflammation

Abstract: Lithium is an effective medication for the treatment of bipolar affective disorder. Accumulating evidence suggests that inflammation plays a role in the pathogenesis of bipolar disorder and that lithium has anti-inflammatory effects that may contribute to its therapeutic efficacy. This article summarizes the studies which examined the effects of lithium on pro-and anti-inflammatory mediators. Some of the summarized data suggest that lithium exerts antiinflammatory effects (e.g., suppression of cyclooxygenase-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
124
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(141 citation statements)
references
References 142 publications
(364 reference statements)
10
124
0
3
Order By: Relevance
“…[14][15][16][17][18][19] Moreover, a large body of data implies that inhibition of inflammation may contribute to the therapeutic effects of psychotropic drugs. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] However, it is important to emphasize that many studies reported opposite findings; namely, that psychotropic drugs also exhibit pro-inflammatory effects. 10,31,[38][39][40][41] Furthermore, the mechanism underlying the anti-inflammatory properties of psychotropic drugs is not fully understood and it is not known whether their influence on inflammation contributes to their therapeutic and toxic effects.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19] Moreover, a large body of data implies that inhibition of inflammation may contribute to the therapeutic effects of psychotropic drugs. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] However, it is important to emphasize that many studies reported opposite findings; namely, that psychotropic drugs also exhibit pro-inflammatory effects. 10,31,[38][39][40][41] Furthermore, the mechanism underlying the anti-inflammatory properties of psychotropic drugs is not fully understood and it is not known whether their influence on inflammation contributes to their therapeutic and toxic effects.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of lithium on FGF23 expression may thus be considered a side effect unrelated to the antidepressant activity of the drug [105]. The observed effect of lithium may, for instance, contribute to the known impact of lithium on inflammation [106]. However, 1,25(OH) 2 D 3 has been shown to be a powerful regulator of mood [107][108][109] and the influence on FGF23 may indirectly modify the neurobiological effects of lithium.…”
Section: Discussionmentioning
confidence: 99%
“…Litijum takođe ispoljava značajno anti-inflamatorno dejstvo, verovatno putem supresije COX-2 ekspresije kao i putem inhibicije stvaranja citokina IL-1β ili TNF-α i putem povećanja sinteze IL-2 i IL-10. (11,12). Moguće je da su promene u jedru u našoj studiji indukovane nekim od signalnih puteva na koje litijum utiče u ćelijama poput G protein /ciklični AMP ili inozitol 3 fosfatnog puta.…”
Section: Diskusijaunclassified